Psychological dimensions of effective leadership - Dereškevičiūtė , Edita (Psichologija, 2000)
Many psychological theories of leadership describe effective leadership in behavioural terms. Consideration and initiating structure are defined as two main dimensions of leader’s behaviour. But it is shown in many researches that cultural peculiarities and characteristics of economy system significantly influence implicit and explicit concepts of effective leadership. The aim of our research is to investigate psychological dimensions of effective leadership behavior on the sample of Lithuanian employees.49 managers and 52 workers participated in our research. Repertory Grid and Critical Incidents technique were used. According to the research data three dimensions of effective leadership were foundl. Work with subordinates.2. Individual-professional features.3. Task-oriented behaviour. Some differences between groups of managers and workers were found in description of effective leadership. Workers tend to emphasise interpersonal communication skills, managers stress task-oriented behaviour. Collected data provide qualitative basis for establishment of adequate criteria of performance appraisals, personnel selection, creation of training programs.